Characterization of 3D Orthogonal Woven Carbon/Kevlar Composite Under Tensile Loading - G, Ram Vishal; Singh, Dalbir; H. V, Srikanth (International Journal of Integrated Engineering, 2023)
In the present work, the tension response of polypropylene (PP) based composites reinforced with Carbon/Kevlar fabrics was investigated. The weft, wrap, and binder are considered in the direction (XYZ) and woven into a 3D fabric. Two homogeneous fabrics with Carbon (CCC), Kevlar (KKK), hybrid Carbon/Kevlar (CCK), and hybrid Kevlar/Carbon (KKC) fabrics were produced using a hand-made spoke frame. The architecture of the fabrics was three-dimensional orthogonal (3D-O). Four different composite laminates were manufactured using a vacuum bag-assisted moulding technique. The tensile loading was applied using a Nano-UTM set-up at travel of +6.25/-3.1 mm and software-automated generation of stress-strain data. The results indicated that the tensile properties of thermoplastic 3D-O composites are sensitive. In all the composites, the peak stress, strength, and modulus were increased when noticed with the 2D fabric. The experimental results show that the tensile strength of CCK and CCC with carbon fibres used in their weft and warp direction was greater than that of KKC and KKK with Kevlar fibres used in fibres weft and warp direction. The hybridization and 3D orthogonal weaving method also increased the tensile strength. The observation were characterized through scanning electron microscope.